2021
DOI: 10.1136/bmjgast-2021-000608
|View full text |Cite
|
Sign up to set email alerts
|

Assessment ofHelicobacter pyloristatus by examination of gastric mucosal patterns: diagnostic accuracy of white-light endoscopy and narrow-band imaging

Abstract: ObjectivesHelicobacter pylori infection is a common cause of chronic gastritis worldwide and an established risk factor for developing gastric malignancy. The endoscopic appearances predicting H. pylori status are an ongoing area of research, as are their diagnostic accuracies. This study aimed to establish the diagnostic accuracy of several mucosal features predictive of H. pylori negative status and formulate a simple prediction model for use at the time of endoscopy.DesignPatients undergoing high-definition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
2
11
1
Order By: Relevance
“…In the present study, there was female predominance (56.4%), which near to the results in the study done by Glover et al (16) who found that (56.9%) of their studied cases were females. But in the study was done by Osman et al (17) there were 36 (61%) males and (39%) females.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, there was female predominance (56.4%), which near to the results in the study done by Glover et al (16) who found that (56.9%) of their studied cases were females. But in the study was done by Osman et al (17) there were 36 (61%) males and (39%) females.…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, The most frequent presentations findings among the studied cases pre therapy was dyspepsia (63.6%) followed by epigastric pain (23.6%), abdominal fullness presented in 12.7% and vomiting (18%) and persistence of the symptoms dyspepsia in 27.3%, abdominal fullness in 10.9% while decrease abdominal pain to 3.6% and vomiting 1.8% which was not following Glover et al (16) who found that Chronic gastritis was the most common endoscopic findings in pre and posttreatment of their studied cases, also in the study was prepared by Calik et al (14) via endoscopic biopsy, 86.8 percent were diagnosed with gastritis, and 13.1 percent were diagnosed with ulcer. Hussein et al (19) discovered that 46.1% had antral gastritis, 24.3% had dyspepsia, and 16.5% had both stomach and duodenal ulcers.…”
Section: Discussioncontrasting
confidence: 49%
“…This study only investigated endoscopic findings that were used in the Kyoto classification score. Further analysis is expected, including other findings related to gastric cancer, such as xanthoma, 38 foveolar hyperplastic polyp, 39 RAC, 40 and fundic gland polyp. 41 Although this study excluded patients who received prior H. pylori eradication therapy, it was found that the H. pylori ‐negative group included H. pylori ‐naïve patients, patients with H. pylori that spontaneously disappeared, and patients who received unintentional H. pylori eradication by antibiotic treatment for other infectious diseases.…”
Section: Discussionmentioning
confidence: 95%
“…Evidence of RAC as an indicator of non-infection has been reported in both in Japan[ 17 , 18 ] and several other countries[ 19 - 21 ], including in the west[ 22 - 24 ], as shown in Table 2 . Two recent meta-analyses reported that the sensitivity and specificity of RAC for predicting non-infection were 78%-80% and 94%-97%, respectively[ 25 , 26 ].…”
Section: H Pylori Infection In the Kyoto Classificationmentioning
confidence: 99%